Propagation of water hyssop ( Bacopa monnieri L.) in vitro - AL-Arady, Haleemah J.; Saleh, Ansam M.; M., Khaun A.; Al-Zewar, Jihad M. (Iraqi Journal of Aquaculture, 2021)
The study aimed to examine the ability of propagation of water hyssop Bacopa monnieri L. in vitro. To induce callus, two auxin , NAA and 2,4-D are used. They showed the highest percentage of 93% callus induction when 1.5 mg .l -1 was used for both. The induced callus was distinguished by its white compact color containing a lot of nodes. After that another treatment with 3 mg . l -1 2,4-D was conducted to score 85% , the callus was compact yellow. The treatment by 3 mg/l -1 NAA scored 53%. The callus was yellow and soft, where as the callus was not induced by hormones free treatment. The effect of cytokines on the formation of vegetative buds was also examined in this study. The results showed that the interaction between treatment by (0.5 mg .l -1) of BA and (0.5 mg.l -1) KN was significantly increased in the number of the vegetative buds; the number was 40 vegetative buds. Then another treatment followed (0.5 mg . l -1) BA, the interaction of (0.5 mg.l -1) BA, KN and NAA and (0.5 mg. l -1) of KN to form (14.7, 10.3, 10.0) vegetative buds respectively. The control treatment scored 2.5 vegetative buds to show a significant increase in the length of the vegetative buds (15.33 cm) followed by the treatment of the interaction between (0.5 mg .l -1) BA and KN to score (13.00 cm) and the treatment of (0.5 mg.l -1) BA , (8.33 cm). The interaction between (0.5 mg. l-1) of BA, KN and NAA, (6.67 cm). The length of the vegetative buds was (4.67 cm) in the treatment by (0.5 mg.l -1) KN. The plants were acclimatized then transformed into the water field successfully.